2019
DOI: 10.1186/s12889-019-7057-x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal decomposition of life years lived with disability in India: a growing demographic concern

Abstract: Background: To draw optimal benefits of the demographic dividend, healthy life years of the young adults is a growing concern in India. Rising prevalence of chronic non-communicable diseases among the younger population is responsible for increasing the life years lived with disability among them and for affecting their productivity in turn. This study measures the disability burden in various Indian sub-populations and assesses the contribution of disability to the change in person years lived with a disabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…A higher disability prevalence and risk difference among educational categories predicts that the impact on disability is much severe among elderly in the selective categories. Study shows non-elderly age-groups have a growing disability burden from a range of conditions that includes communicable diseases, NCDs and injuries (13). Besides, the trend in the incidence of injuries, atrocities in childhood, malnourishment at the early ages, and violence among children and younger age adults are also seeking an attention in the context of India for upcoming decades.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A higher disability prevalence and risk difference among educational categories predicts that the impact on disability is much severe among elderly in the selective categories. Study shows non-elderly age-groups have a growing disability burden from a range of conditions that includes communicable diseases, NCDs and injuries (13). Besides, the trend in the incidence of injuries, atrocities in childhood, malnourishment at the early ages, and violence among children and younger age adults are also seeking an attention in the context of India for upcoming decades.…”
Section: Discussionmentioning
confidence: 99%
“…An improvement in health, as well as disability outcomes among children, has been noticed in recent decades (12). However, an increase in disability among working age-groups in states like Uttar Pradesh, Karnataka, Punjab has also been pointed out in the duration of 2001-11 (13). Disability contributed by those population is substantial to add longer years with disability in the population, and hence, creates a long-term burden on the healthcare system.…”
mentioning
confidence: 99%
“…Therefore, the states with a higher share of the older population are more likely to have a diseased population. On the other hand, states with younger populations have also witnessed a paradigm shift in the age at the onset of the disease; rising prevalence of chronic NCDs among the younger population is responsible for increasing the life years lived with disability among them and for affecting their productivity in turn (Banerjee et al, 2019;Mohanty et al, 2021). Bhise et al (2018) studied the NSSO 71st round and found the highest prevalence of NCD in southern states (107/1,000), and the lowest was recorded in the northeast (11/1,000) (Bhise et al, 2018).…”
Section: Demographic Determinantmentioning
confidence: 99%
“…First, the aging population is more vulnerable to NCDs, and increased life expectancy does not necessarily convert into healthy years (LASI Wave 1 Report, 2020). Second, the increasing prevalence of chronic NCDs among younger individuals is accountable for a rise in the years lived with disability among this age group, consequently impacting their productivity (Banerjee et al, 2019;Mishra et al, 2021;Mohanty et al, 2021). The burden of NCDs causes severe socioeconomic impacts in India, whereas the diversity in SED across regions leads to diversity in the prevalence of the diseases, hence broadening the role of SED statistics from explaining health patterns to actively forecasting the distribution within the nation.…”
Section: Introductionmentioning
confidence: 99%